Near-infrared hyperspectral imaging for predicting the quality of SO2 pre-treated and dehydrated mango - Aozora, Wayan Dipasasri; Tantinantrakun, Achiraya; Thompson, Anthony Keith; Teerachaichayut, Sontisuk (My University, 2025)
Prediction for quality indices of SO2 pre-treated and dehydrated mango was accessed by NIR-HSI. Models for predicting TSS and SO2 content achieved R = 0.82; RMSEP = 2.42% and R = 0.83; RMSEP = 56.40 mg/kg, respectively. Visualization of TSS and SO2 content could be presented by predictive images.
Keywords: Image; Non-destructive; Prediction; Quality; Spectra